Active shape reconstruction using a novel visuotactile palm sensor - Jingyi Hu; Shaowei Cui; Shuo Wang; Rui Wang; Yu Wang (Biomimetic Intelligence and Robotics)
Tactile sensing enables high-precision 3D shape perception when vision is limited. However, tactile-based shape reconstruction remains a challenging problem. In this paper, a novel visuotactile sensor, GelStereo Palm 2.0, is proposed to better capture 3D contact geometry. Leveraging the dense tactile point cloud captured by GelStereo Palm 2.0, an active shape reconstruction pipeline is presented to achieve accurate and efficient 3D shape reconstruction on irregular surfaces. GelStereo Palm 2.0 achieves a spatial resolution of 1.5 mm and a reconstruction accuracy of 0.3 mm. The accuracy of the proposed active shape reconstruction pipeline reaches 2.3 mm within 18 explorations. The proposed method has potential applications in the shape reconstruction of transparent or underwater objects.